The Implementation of the SOEs Partnership Program on the empowerment of MSMEs in Banjarbaru City - Sudirwo S.E., M.M. (Jurnal Ilmiah Ekonomi Bisnis, 2020)
The Partnership Program is a revolving aid distribution program from State-Owned Enterprises (SOEs) towards the economic development of the community, especially micro small and medium enterprises (MSMEs), which focuses on capital aspects. This research is to describe the implementation of the SOEs Partnership Program on the empowerment of MSMEs in Banjarbaru City. This type of research is qualitative research with a case study design. Data collection techniques are in-depth interviews with certain informants with informants deliberately chosen include program coordinators in 3 (three) SOEs, namely PT Telkom Witel Banjarmasin, PT Pelindo III Regional Kalimantan, and PT Pegadaian Banjarmasin, then participant observation of fostered partners, and documentation studies. The results of this research indicate that the implementation of the SOEs Partnership Program is running effectively to increase the efforts of MSMEs to be strong and independent. There are two forms of activities in the SOEs Partnership Program, namely granting loans with administrative services 3 percent per year and grants in the form of coaching, training, apprenticeship, and exhibitions for fostered partners. However, there are weaknesses found among others (1) the absence of partner partners for coaching on an ongoing basis, (2) many MSMEs do not know with the program, and (3) the attitude of the fostered partners who are still lacking discipline in payment. The expectation of this research is to be able to complete the existing SOEs evaluation report and provide input so that it can improve better performance.